Principles of corporate finance - Brealey, Richard A.; Myers, Stewart C; Allen, Franklin; Mohanty, Pitabas (New Delhi Mc Graw Hill, 2019)
Designed for courses in corporate finance taught at the MBA and undergraduate level, this text offers in-depth treatment of modern finance theory giving clear explanations of the capital asset pricing model, its strengths and weaknesses.
Keywords: Corporations--Finance; Business enterprises--Finance--Management